في الترجمة اللّسانية وترحيل المعرفة السوسيرية الجديدة إلى اللّسان العربي - بن وناس, مفيدة (جامعة الوادي - university of Eloued, 2022)
تشكل الترجمة ركنا رئيسا في عملية إثراء المعرفة اللسانية، فهي رافد يغني الألسنة بالمصطلحات والتراكيب الجديدة، ويؤكد كينونة اللسان بدخوله في تفاعل مع الألسنة الأخرى، وتتزايد أهميتها اليوم بشكل متسارع في رحاب الفضاء الاتصالي الراهن، الذي أتاح للباحث العربي الانفتاح على اللّسانيات الغربية ومواكبتها في وقت وجيز متزامن، وهذا ما حدث مع "لسانيات سوسير الجديدة"، فقد اطلع الدارسون على نصوصه المكتشفة التي باتت موضوع بحث ونظر، وبذلوا جهودا لتقديمها للقارئ العربي، من خلال المؤلفات العربية التي صدرت حولها، وترجمة الكتابات اللسانية الغربية الرائدة التي بحثت فيها، والأهم ترجمة نصوص سوسير الجديدة التي تم تحقيقها ونشرها بعنوان (Écrits de linguistique général) سنة 2002 وفي ضوء ما تكشف لنا من ترجمات سنبين كيف تم ترحيل المعرفة اللسانية السوسيرية الجديدة إلى اللسان العربي. Abstract: Translation constitutes a major pillar in the process of enriching linguistic knowledge, as it is a tributary that enriches tongues with new terms and structures, and confirms the language’s being by entering into interaction with other tongues. Briefly simultaneous, this is what happened with Saussure's 'neo-linguistics' Scholars have looked at his discovered texts, which were the subject of research and consideration, and made efforts to present them to the Arab reader, through the Arabic literature that was published about them, and the translation of the pioneering Western linguistic works that I researched, and most importantly the translation of the new Saussure texts that were investigated and published under the title of the year 2002 and in the light of what was revealed. From our translations, we will show how the new Sussian linguistic knowledge was transferred to the Arabic language.
مقال
Keywords: الترجمة؛ النصوص الجديدة؛ سوسير؛ اللسان العربي; Translation, new texts, saussure, Arabic tongue